Two new species of Manihot (Euphorbiaceae) from the Amazon region - Mendoza F., J. Moises; Orlandini, Priscila; Martins, Márcio Lacerda Lopes (Phytotaxa, 2020)
Two new species of Manihot endemic to the Amazon region are described here: Manihot australis and M. striata. Important diagnostic characters distinguishing the new species such as presence or absence of indumentum, form and size as well presence or absence of ribs in fruits, among other, are discussed and illustrated by line drawings and photographic plates. Information about their natural habitat and distribution is also provided.